2016
DOI: 10.3390/languages1020010
|View full text |Cite
|
Sign up to set email alerts
|

Listening for Imagery by Native Speakers and L2 Learners

Abstract: Slobin's thinking-for-speaking (TFS) hypothesis suggests that speakers are habitually attuned to aspects of an event that are readily codable in the language while they are formulating speech. This TFS process varies considerably cross-linguistically and can be observed in all forms of production and reception including listening for understanding or mental imagery. This study explored whether second language learners (L2) engage in mental simulation of deictic paths while processing motion language online. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Similar to the patterns of L1 mental imagery, both compatibility (Ahn & Jiang, 2018;Dudschig et al, 2014;Koster et al, 2018;Tomczak & Ewert, 2015) and interference effects (Bergen et al, 2010;Buccino et al, 2017;Vukovic & Williams, 2014;Wheeler & Stojanovic, 2006) have been found in L2 mental imagery research. However, some studies have reported no effects or attenuated effects in L2 mental imagery relative to L1 mental imagery (Chen et al, 2019;Norman & Peleg, 2022;Wu, 2016) due to a reduced degree of embodiment in an L2 compared to L1 (Foroni, 2015), or the formation of different mental representations in L1 and L2 (Dudschig et al, 2014;Monaco et al, 2019). Most existing studies using linguistic and visual stimuli support the perceptual-motor activation in L2 processing, covering various aspects like size and orientation (Koster et al, 2018), shape (Ahn & Jiang, 2018), motion (Tomczak & Ewert, 2015) and emotion (Dudschig et al, 2014;Foroni, 2015).…”
Section: Mental Imagery In L2 Processingmentioning
confidence: 99%
“…Similar to the patterns of L1 mental imagery, both compatibility (Ahn & Jiang, 2018;Dudschig et al, 2014;Koster et al, 2018;Tomczak & Ewert, 2015) and interference effects (Bergen et al, 2010;Buccino et al, 2017;Vukovic & Williams, 2014;Wheeler & Stojanovic, 2006) have been found in L2 mental imagery research. However, some studies have reported no effects or attenuated effects in L2 mental imagery relative to L1 mental imagery (Chen et al, 2019;Norman & Peleg, 2022;Wu, 2016) due to a reduced degree of embodiment in an L2 compared to L1 (Foroni, 2015), or the formation of different mental representations in L1 and L2 (Dudschig et al, 2014;Monaco et al, 2019). Most existing studies using linguistic and visual stimuli support the perceptual-motor activation in L2 processing, covering various aspects like size and orientation (Koster et al, 2018), shape (Ahn & Jiang, 2018), motion (Tomczak & Ewert, 2015) and emotion (Dudschig et al, 2014;Foroni, 2015).…”
Section: Mental Imagery In L2 Processingmentioning
confidence: 99%